African Americans' Perceptions of Prostate-Specific Antigen Prostate Cancer Screening. (August 2015) - Hunter, Jaimie C.; Vines, Anissa I.; Carlisle, Veronica
Background . In 2012, the U.S. Preventive Services Task Force released a hotly debated recommendation against prostate-specific antigen testing for all men. The present research examines African Americans' beliefs about their susceptibility to prostate cancer (PCa) and the effectiveness of prostate-specific antigen testing in the context of the controversy surrounding this recommendation. Method . This study used a qualitative design to examine perceptions regarding susceptibility and screening. Data were collected at a community health center and three predominantly African American churches in North Carolina. Study participants were 46 African American men and women who attended one of four "listening sessions" for pretesting PCa educational materials (average age = 55 years). Listening sessions of 1.5-hour duration were conducted to pretest materials; while presenting the materials, researchers probed beliefs and knowledge about PCa screening. The sessions were recorded and transcribed, and the transcripts were qualitatively analyzed using grounded theory. Results. The four emergent themes indicated that participants (1) cited behavioral, psychosocial, and biological reasons why African American men have higher PCa risk compared with others; (2) knew about the controversy and had varying responses and intentions; (3) believed screening could save lives, so it should be used regardless of the 2012 recommendation; and (4) felt that women can help men go to the doctor and make screening decisions. Conclusion. Health education efforts to help community members understand health controversies, screening options, and how to make informed screening decisions are critical.